Enhanced catalytic activity of copper complexes in microgels for aerobic oxidation of benzyl alcohols. Issue 42 (1st May 2020) - Schäfer, Dominic; Fink, Fabian; Kleinschmidt, Denise; Keisers, Kristina; Thomas, Fabian; Hoffmann, Alexander; Pich, Andrij; Herres-Pawlis, Sonja
Abstract : Catalytically active copper bis(pyrazolyl)methane complexes have been anchored into pVCL-GMA microgels on specified positions within the microgel network. Abstract : Catalytically active copper bis(pyrazolyl)methane complexes have been anchored into pVCL-GMA microgels on specified positions within the microgel network. Functionalized microgels act as nanoreactors providing a tailored environment and stabilization for the copper complexes thus increasing the product yield. The oxidation of benzyl alcohols to their respective aldehydes was chosen as a test reaction to show the enhancement of catalytic activity due to the immobilization of the copper complex compared to the copper salt and the molecular copper complex.